A organização do meio social educativo de uma turma de educação infantil ribeirinha da Amazônia: um estudo à luz da teoria de Vigotski - OLIVEIRA, Luciana da Costa (Universidade Federal do Pará, 2019)
This dissertation consists of a study about the organization of the educational social environment of a children's education group in a public school in the community of Caruaru, on the Island of Mosqueiro, linked to the Municipal Secretary of Education of Belém do Pará. Vygotsky's theory. In the perspective of this author, people are constituted as subjects through their social relations and it is up to the school education to organize the social relations experienced by the children in the school, so as to intervene in their processes of human formation in a critical and emancipatory perspective. Thus, this research had as objective to analyze which educational social environment contributes to the formation of the conscious personality of the children of a class of children's education riverside of the Amazon. The investigation was divided into two stages. The first stage consisted of the observation of the organization of the educational social environment. The information in this stage was produced through observation, semi-structured interview with the teacher, meeting with the families of the children and analysis of the School's Political Pedagogical Project. The second stage consisted in the execution of the collaborative action to contribute to the pedagogical practice of the teacher regarding the organization of the social educational environment of the class, in order to collaborate for the process of social formation of the conscious personality of the children. The production of information in this stage was accomplished by means of study sessions, elaboration and execution of a planning with the teacher and the children. In both steps, field journal annotations and audiovisual and photographic recordings were carried out, in order to ensure the study of the processes, according to the way of proceeding the analysis by the genetic-causal method postulated by Vigotski. The results obtained in the first stage pointed out that the teacher had as theoretical basis the theory of Vygotsky and the ideas of Paulo Freire, but had no training in the perspective of riverside education. He had participated in a course in the level of improvement in early childhood education and perhaps because of this, he organized the educational social environment listening to the children and taking into account their particular life peculiarities, their knowledge and experiences, as well as the peculiarities of childhood. In the second stage, the results showed that the collaborative action contributed to the organization of the educational social environment, potentializing the pedagogical practice and the formation of the conscious personality of the children. It is concluded that the concept of educational social environment formulated by Vygotsky, if taken together with the conceptual system of the author and with the conceptions defended by the scholars of riverside education, can contribute with the teacher in his historical task of thinking and organize a critical early childhood education for and with the riverside children of the Amazon.